International Perspectives : the Future of Nonhuman Primate Resources : Proceedings of the Workshop Held April 17-19, 2002 (Online access: NCBI NCBI Bookshelf., 2003)
The future of nonhuman primate (NHP) resources is a concern of scientists, veterinarians, and funding authorities. An April 2002 workshop brought participants from all over the world to discuss various aspects of the issue such as current shortfalls and e.